Visualization study on the uniformity of refrigerant distribution in parallel multi-channels. (August 2022) - Huang, Yuqi; Wei, Caifeng; Wang, Shun; Lu, Yiji
Graphical abstract: Highlights: The phase separation in the header and branch channels is captured and analysed. A method for calculating void fraction is proposed by OpenCV graphics processing. The lower inlet method can achieve the best two-phase distribution in channels. Reducing inlet quality and inlet mass flux can achieve improved phase distribution. The average void fraction is usually positively correlated with pressure gradient. Abstract: Heat pump technology is a battery thermal management technology with considerable potential and which has obvious advantages in environmental adaptability and energy saving. The small-channel heat exchanger is an important part of the heat pump system, and the uniformity of the two-phase refrigerant in the header and branch channels is one of the key issues that restrict the performance of the system. In this paper, a two-phase flow visualization phase separation experimental platform, with R1233zd(E) as the working fluid, was established to study the refrigerant distribution in small parallel multi-channels (3 mm). Three inlet configurations are designed, and two types of operating conditions are tested. Moreover, the gas-liquid two-phase boundary in channels is extracted to calculate the average void fraction based on the OpenCV graphics processing function libraries. The key conclusions of the current study are as follows: (1) The two-phase distribution uniformity under the lower inlet method is improved by 50–90% compared with the middle inlet and upper inlet methods. (2) A superior gas-liquid two-phase distribution in channels can be achieved under lower inlet quality (0.01) and lower inlet mass flux (300 kg/(m 2 s)). (3) The average void fraction in each channel is almost always positively correlated with the average pressure gradient.